Relationship between social media addiction and healthy lifestyle behaviors of nursing students - Akalın, Ayşe (Journal of Dependence, 2022)
Objective: The study aims to determine the relationship between social media addiction and healthy lifestyle behaviors of nursing students.Method: This descriptive and correlational design study was conducted with 313 nursing students. Data were collected using Questionnaire Form, Social Media Addiction Scale-Student Form (SMAS-SF) and Healthy Lifestyle Behavior Scale-II (HLBS-II).Results: The mean total scores students’ on the SMAS-SF and HLBS-II were 67.65±17.95 and 140.67±22.77, respectively, indicating students’ social media addictions were low and their healthy lifestyle behaviors were moderately-high. It was found that the mean of SMAS-SF mean scores of the students who are with poor academic achievement, having a high daily social media usage time, with poor health perception, stated social media affects health, were higher. It was also found that the mean of HLBS-II mean scores of the students who are with good academic achievement, and with good health perception, were higher. A negative, significant correlation was found between SMAS-SF and HLBS-II total mean scores.Conclusion: Educational programs need to be prepared to reducing the use of social media and to increase healthy lifestyle behavior of nursing students.
Keywords: Social media; nursing students; addiction; healthy lifestyle